Mitigation measures during elections and it’s impacts on COVID-19 pandemic: Sabah State (Malaysia), New Zealand and the United States - Syaza Putri Zainudin; Mohd Amiruddin Mohd Kassim; Nor Nadia Mohamad Ridza (Penerbit UMS, 2022)
Background and Objective: Countries all over the world respect the election process as one of the fundamental steps in forming a government. However, the exponential spread of COVID-19 has been deeply alarming, with a high number of positive cases and total deaths, forcing World Health Organization to declare it as a pandemic on 11th March 2020. During these unprecedented events, governments have had a tough decision to balance between the constitutional obligation to hold an election and the safety of the people. As such, electoral commissions have implemented numerous approaches to allow election to proceed in a safe and controlled setting during the pandemic. Methods: The preventative measures and standard operating procedures in the Sabah state of Malaysia, New Zealand and the United States elections are discussed, as well as COVID-19 post-election situation in respective countries. Innovative approaches and election flexibilities shall be considered to allow voting in the safest way possible, following the new normal. Discussion: Nevertheless, countries need to evaluate its strength of public health response when deciding to hold elections due to potential devastating outbreaks following elections despite measures taken. Conclusion: The election is a fundamental process in a democracy. Countries are required to be flexible and innovative in their approach to hold a safe election. Nevertheless, it may be prudent for countries with fewer resources and poor pandemic control to postpone election as a rise in cases will be catastrophic, putting many lives at risk.